Modern View on the Role of Epidermal Barrier in Atopic Phenotype Development in Children - Nikolay N. Murashkin; Alena A. Savelova; Roman A. Ivanov; Dmitri V. Fedorov; Leonid A. Opryatin; Wasel Ahmad ("Paediatrician" Publishers LLC, 2020)
Epidermal barrier is one is one of the most important structures of the skin, it performs protective function, ensure internal environment constancy by selective ions and molecules transport and by transepidermal water loss regulation. The biochemical basis of the epidermal barrier consists of complex, integrated and balanced molecular processes leading to keratinocytes death due to terminal differentiation and plasma membrane replacement with horny insoluble macromolecular stratum corneum. Filaggrin and tight junctions (TJs) proteins are important structural components of the epidermal barrier. Filaggrin, after hydrolysis, maintains pH level, preserves water, protects the skin from microbial agents. Whereas TJs proteins with active expression regulate epidermis permeability and create the barrier for exterior antigens.